2016
DOI: 10.1187/cbe.16-07-0212
|View full text |Cite|
|
Sign up to set email alerts
|

Student Buy-In to Active Learning in a College Science Course

Abstract: Student buy-in as a key mechanism for student engagement and performance in an active-learning context is explored. This paper provides the first operational definition of student buy-in to in-class activities, in this case characterizing the complex nature of students’ responses in an active-learning classroom.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
146
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 117 publications
(148 citation statements)
references
References 60 publications
1
146
0
1
Order By: Relevance
“…For example, one study investigating what types of expectations students had about pedagogy in college STEM classes found that first-year students expected more active-learning techniques to be used than non-first-year students (Brown et al, 2017). Furthermore, using surveys has been an effective way of measuring student buy-in and engagement with STEM classes (Brazeal et al, 2016;Cavanagh et al, 2016). These studies revealed that students think that active-learning teaching strategies support their learning in class and lead them to engage in more self-regulated learning habits out of class, such as meeting with other students to complete assignments.…”
Section: Discussionmentioning
confidence: 99%
“…For example, one study investigating what types of expectations students had about pedagogy in college STEM classes found that first-year students expected more active-learning techniques to be used than non-first-year students (Brown et al, 2017). Furthermore, using surveys has been an effective way of measuring student buy-in and engagement with STEM classes (Brazeal et al, 2016;Cavanagh et al, 2016). These studies revealed that students think that active-learning teaching strategies support their learning in class and lead them to engage in more self-regulated learning habits out of class, such as meeting with other students to complete assignments.…”
Section: Discussionmentioning
confidence: 99%
“…Student perceptions of AL are also important and can influence whether faculty implement such practices in their courses; concern that students will avoid their courses due to more “difficult” or involved coursework or students simply not liking the technique have prevented some faculty from implementing pre-prepared AL modules (14). Students themselves may perceive that they learn and retain information better through AL, however this doesn’t necessarily mean that they like or fully engage in classes that implement AL (15,17,19,20). Much of this resistance seems to stem from the desire to passively acquire information from an expert – the instructor – which is perceived to require less effort than actively constructing their own knowledge and dealing with the uncertainty of having the “right” answer, in spite of the fact that these are features not only of AL, but also of the scientific process in general (17,19).…”
Section: Introductionmentioning
confidence: 99%
“…This prior work focusing on summative assessments suggests that student perceptions regarding the purpose and benefits of FAs could impact student interactions with FAs and the learning that results. If students understand and value how particular FA methods can facilitate their learning (i.e., if they “buy into” their use), then they may be more likely to put more effort into completing and using them in productive ways (Cavanagh et al , 2016). Conversely, if students view these methods as unhelpful or irrelevant to their learning, they may choose to engage with FAs in superficial ways that undermine learning (e.g., rushing through them or copying answers from the Internet).…”
Section: Introductionmentioning
confidence: 99%